Translation, cultural adaptation, initial reliability, and validation of the kidney disease and quality of life-short form (KDQOL-SF 1.3) in Turkey - İŞCİ, EMRE (ELSEVIER SCIENCE INC, 2007)
Health-related quality of life (HRQoL) is an important factor that can interfere with treatment outcomes. The aim of the present study was cultural adaptation, validation, and translation of the Mdney Disease Quality of Life-Short Form (KDQoL-SF 1.3) questionnaire into Turkish for the Turkish population. The KDQOL-SF was translated into Turkish and back-translated into English. Patient difficulties in understanding the questionnaire were evaluated and solved by a panel of experts. Measurement properties such as reliability and validity were determined by applying the questionnaire to 82 patients on dialysis, who were randomly selected from the dialysis units of 3 educational and research hospitals in Istanbul: 65% were females; mean patient age was 51 +/- 12 years. The most common primary causes of renal failure were glomerulonephritis (47%), hypertension (31%), and diabetes (7%). The median time on dialysis among the patients was 3 years. Test and retest methods were used for reliability. The total test-retest reliability Cronbach alpha coefficient of the Turkish KDQOL-SF questionnaire was 0.84 to 0.91. These coefficients were statistically significant (P < .05) for 19 dimensions of the KDQOL-SF that ranged from 0.75 to 0.91. The Cronbach alpha coefficient was higher than 0.80 for most components. To evaluate its construct validity, the KDQOL-SF was compared with the Turkish version of the 15D, an instrument for global assessment that contains 15 items divided into 5 dimensions. The scores range from 0 to 1 (0 = worse health status, I = better health status). Significant correlations were observed between the scores of the similar domains of the 15D and the KDQOL-SF. The best correlations were observed between physical functioning (KDQOL-SF) and mobility (15D; r = -.810) and between emotional well-being of (KDQOL-SF), and with the mental functions of 15D; (r = -.784), sexual function (KDQOL-SF) and sexual activity (15D; r = -.781), and patient satisfaction and distress (r = -.801). These findings support the construct validity of the new Turkish adapted KDQOL-SF. This study is reporting the complete process of translation and validation of the KDOOL-SF in the literature. These results demonstrate the high reliability and validity of this questionnaire for Turkish patients on dialysis.
Keywords: OF-LIFE; INSTRUMENT